Hydrogeochemistry of Natar and Cisarua Hot springs in South Lampung, Indonesia - Mochamad Iqbal; Bella Restu Juliarka; Wijayanti Ashuri; Bilal Al Farishi (UIR PRESS, 2019)
Natar Hot Spring is one of the geothermal manifestations that is located in Lampung Province, Indonesia. About 6 km to the east, another hot spring appears with temperature around 40°C with neutral pH called Cisarua Hot Spring. The Natar Hot Spring itself having temperature 47-54°C with 6.23 pH. Based on the geologic map, the appearance of these hot spring is caused by Lampung-Panjang Fault which trending northwest-southeast. Morphology of the research area is showing a flat terrain topography which composed of Quaternary volcanic rock and metamorphic rock in the basement. The nearest volcano that expected to be the heat source of the geothermal system is the Quaternary extinct volcano called Mt. Betung which is located about 15 km to the southwest. The aim of the study is to analyze the geochemistry of the manifestations and calculate the reservoir temperature. Geochemistry analysis result shows both manifestations are bicarbonate which is formed as a steam-heated water or steam condensates. Geothermometer calculation shows that the geothermal reservoir has temperature 150-160°C with approximately 300 m in depth. All manifestations are originated from meteoric water according to stable isotope analysis D and δ18O data and interacting with carbonate-metamorphic rock beneath the surface based on 13C isotope value. A further geophysics study is needed to determine where the heat comes from.